Characterization and Remediation of Chlorinated Volatile Organic Contaminants in the Vadose Zone. Issue 4 (15th February 2013) - Brusseau, Mark L.; Carroll, Kenneth C.; Truex, Michael J.; Becker, David J.
Abstract : Contamination of vadose‐zone systems by chlorinated solvents is widespread and poses significant potential risk to human health through impacts on groundwater quality and vapor intrusion. Soil vapor extraction (SVE) is the presumptive remedy for such contamination and has been used successfully for innumerable sites; however, SVE operations typically exhibit reduced mass‐removal effectiveness at some point due to the impact of poorly accessible contaminant mass and associated mass‐transfer limitations. Assessment of SVE performance and closure is currently based on characterizing contaminant mass discharge associated with the vadose‐zone source and its impact on groundwater or vapor intrusion. These issues are addressed in this overview, with a focus on summarizing recent advances in our understanding of the transport, characterization, and remediation of chlorinated solvents in the vadose zone. The evolution of contaminant distribution with time and the associated impacts on remediation efficiency are discussed, as is potential impact of persistent sources on groundwater quality and vapor intrusion. In addition, alternative methods for site characterization and remediation are addressed.